Implementasi Standar Penilaian Dalam Pembelajaran PAI pada Kurikulum 2013 di SMP Pahlawan Nasional Kecamatan Medan Tembung - Neliwati; Hazrat , Mhd; Salsabila, Afifah; Nia, Rizky (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Assessment Standards are criteria regarding mechanisms, procedures, and instruments for assessing student learning outcomes. Assessment standards by educators according to BSNP include general standards, planning standards, implementation standards, standards for processing and reporting assessment results as well as standards for utilizing assessment results. The focus of this research is around the implementation of assessment standards by Islamic Religious Education (PAI) teachers at The National Hero Junior High School, Medan Tembung District. This research uses an interview method using descriptive and qualitative approaches to describe and analyze phonetics, events, social activities, attitudes, beliefs, perceptions, thoughts of people individually and in groups, and is supported by Library Research by collecting various references from books, journals, and supporting scientific papers.The purpose of this study is to find out how the assessment process in learning Islamic Religious Education at SMP Pahlawan Nasional to students and find out what things should be assessed from students based on the 2013 curriculum. The result of this study is that the assessment carried out by Islamic Religious Education teachers prioritizes the Affective, Cognitive, and Psychomotric aspects of these students. The Affective Aspect is more emphasized in learning, because this aspect is very important considering that the learning of Islamic Religious Education is closely related to attitude, character, and ethics.